1999
DOI: 10.1159/000012326
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Release Lanreotide Treatment in Acromegaly: Effects on Quality of Life

Abstract: Background: It is not known whether medical treatment to lower growth hormone (GH) and insulin-like growth factor (IGF)-1 levels may improve the compromised quality of life of patients with acromegaly. Methods: We studied the effects on quality of life of the slow-release somatostatin analogue lanreotide, 30 mg i.m., every 14 days for 2 months in 10 patients with active acromegaly (8 females/2 males, mean age 57.3 ± 11.4). Hormone measurements and psychometric evaluation by means of self-rating scales were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…Hormone measurements and psychometric evaluation by means of self-rating scales were carried out at the baseline and after 1 and 2 months. Together with a significant decrease in GH and IGF-I, treatment with lanreotide significantly improved symptoms relating to psychological distress, well-being and social fears by employing the Symptom questionnaire, the Cognitive Scale of the screening List for Psychosocial Problems by Kellner and the Social Situation Questionnaire by Marks (21). Another small prospective study assessing various outcome measures including quality of life in nine patients with newly diagnosed acromegaly treated with octreotide-LAR for 6 months demonstrated significantly improvements in health perception and fatigue (22).…”
Section: Discussionmentioning
confidence: 99%
“…Hormone measurements and psychometric evaluation by means of self-rating scales were carried out at the baseline and after 1 and 2 months. Together with a significant decrease in GH and IGF-I, treatment with lanreotide significantly improved symptoms relating to psychological distress, well-being and social fears by employing the Symptom questionnaire, the Cognitive Scale of the screening List for Psychosocial Problems by Kellner and the Social Situation Questionnaire by Marks (21). Another small prospective study assessing various outcome measures including quality of life in nine patients with newly diagnosed acromegaly treated with octreotide-LAR for 6 months demonstrated significantly improvements in health perception and fatigue (22).…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies investigated the effects of SSTA on QoL and concluded that improvement of symptoms relating to psychological distress, well-being, social fears, and QoL occurs after treatment with Lanreotide (18,19). However, these studies did not compare the effects on QoL with other treatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms and morbidity associated with acromegaly have a significant impact on patients’ health-related quality of life (HRQoL), but few studies have taken HRQoL into account as a measuring instrument for patients with this condition [1]. Diagnosis of acromegaly is often delayed by several years, when changes in appearances as well as in many internal tissues may not be reversible, even after successful treatment.…”
Section: Introductionmentioning
confidence: 99%